A randomised controlled trial to assess whether prehabilitation improves fitness in patients undergoing neoadjuvant treatment prior to oesophagogastric cancer surgery: study protocol. Issue 12 (22nd December 2018) - Allen, Sophie; Brown, Vanessa; Prabhu, Pradeep; Scott, Michael; Rockall, Timothy; Preston, Shaun; Sultan, Javed
Abstract : Introduction: Neoadjuvant therapy prior to oesophagogastric resection is the gold standard of care for patients with T2 and/or nodal disease. Despite this, studies have taught us that chemotherapy decreases patients' functional capacity as assessed by cardiopulmonary exercise (CPX) testing. We aim to show that a multimodal prehabilitation programme, comprising supervised exercise, psychological coaching and nutritional support, will physically, psychologically and metabolically optimise these patients prior to oesophagogastric cancer surgery so they may better withstand the immense physical and metabolic stress placed on them by radical curative major surgery. Methods and analysis: This will be a prospective, randomised, controlled, parallel, single-centre superiority trial comparing a multimodal 'prehabilitation' intervention with 'standard care' in patients with oesophagogastric malignancy who are treated with neoadjuvant therapy prior to surgical resection. The primary aim is to demonstrate an improvement in baseline cardiopulmonary function as assessed by anaerobic threshold during CPX testing in an interventional (prehab) group following a 15-week preoperative exercise programme, throughout and following neoadjuvant treatment, when compared with those that undergo standard care (control group). Secondary objectives include changes in peak oxygen uptake and work rate (total watts achieved) at CPX testing, insulin resistance, quality of life, chemotherapy-related toxicity and completion, nutritional assessment, postoperative complication rate, length of stay and overall mortality. Ethics and dissemination: This study has been approved by the London-Bromley Research Ethics Committee and registered on ClinicalTrials.gov. The results will be disseminated in a peer-reviewed journal. Trial registration number: NCT02950324 ; Pre-results.